Perception of Summer Conditions in Prefabricated Multifamily Buildings Occupied by Middle-Aged and Elderly People Based on Monitoring of Dwellings in Warm-Summer Humid Continental Climate - Magdalena Grudzińska; Rafał Stabryła; Krzysztof Siwek; Krzysztof Bartoszek; Jakub Wankiewicz (Applied Sciences)
This study concentrates on the thermal comfort in dwellings occupied by people above 45 years old in buildings constructed of prefabricated large-scale concrete plates. The buildings underwent many thermal modernisations, and nowadays, with growing external temperatures and solar irradiation, their properties may not be sufficient to ensure comfortable internal conditions. The issue is all the more important because the population of residents is growing older, so the occupants are becoming more vulnerable and more prone to the negative effects of overheating. This research included the monitoring of ten apartments located in five- or twelve-storey buildings, situated in Lublin, a city in southeastern Poland. The monitoring took place in July and August 2023, when internal temperature, solar radiation intensity, window opening, and shading strategies were measured and observed. External conditions were registered by meteorological posts belonging to the Maria Curie-Skłodowska University in Lublin. Additional information about the inhabitants’ behaviour and internal gains was collected through a questionnaire. In most cases, dwellings located in prefabricated residential buildings could be maintained in a comfortable temperature range, even by the ageing self-sufficient occupants. Still, when particular negative factors related to the building’s construction appeared, overheating could be noticeably longer and more troubling, exceeding the elderly’s capabilities to handle it. This showed the necessity of further analyses, especially in the context of the global warming effect.